10-year stability of magnetite nanopowder prepared by the exploding wire method: is it a useful feature for environment safety and biomedical applications? - I. A. Khlusov; A. S. Omelyanchik; V. V. Rodionova; V. V. Shupletsova; O. G. Khaziakhmatova; K. A. Yurova; L. S. Litvinova; I. K. Norkin (Бюллетень сибирской медицины)
Aim. To analyze the structural, magnetic, and cytotoxic features of magnetite nanoparticles (MNPs) prepared by the exploding wire method and stored in a dark place at ambient temperature (65 ± 15% humidity, air pressure 760± 20 mm Hg., temperature 22 ± 4 °C) for 10 years.Materials and methods. The properties of MNPs were analyzed by X-ray diffraction (XRD), transmission electron microscopy (TEM) and selected area electron diffraction (SAED), and vibrating-sample magnetometer (VSM). Viability of human blood mononuclear leukocytes was determined using 0.4% trypan blue staining after 24-hour culture with the nanopowder.Results. The calculated size of the particles remained almost unchanged after 10 years of storage. The XRD and SAED patterns showed that crystallinity was preserved for 10 years. The diameter of the crystalline component of MNPs (DXRD) was close to the particle size determined by TEM. It confirms high crystallinity of the tested nanoparticles. Saturation magnetization (MS) of the MNP powder after 10 years of storage was unexpectedly higher than that of the as-prepared MNP powder. Reduced remanent magnetization (MR / MS) was equal for both samples within the margin of error. No cytotoxic effect of MNPs in vitro was detected in the long-term study.Conclusion. No dramatic changes in the structural, magnetic, and cytotoxic features of MNPs were noted after 10 years of storage. It indicated 10-year stability of MNP powder that may be a useful feature for environment safety and biomedical applications.